Breeding for large seed size in sesame (Sesamum indicum L.): Breeding for large seed size in sesame (Sesamum indicum L.) - S T PONSIVA; A P T RAJKAPUR HARTIABINESARAJA; S PRAVEENKUMAR; S SELVAMANI; N SENTHILKUMAR; S THIRUGNANAKUMAR (Journal of Oilseeds Research, 2020)
During the year 2018-2019 a total of three F2 generation population was evaluated during rabi season. The experiment was conducted in randomized block design replicated twice. Observations were recorded on the yield and yield contributing traits. Heterobeltiosis up to a maximum of 96.4% was recorded for seed length, 92.98% for seed breadth, 101.98% for thousand seed weight, 109.81% for thousand seed volume, 111.55% for seed density, 117.19% for oil content and 137.63% for seed yield per plant. The result indicated that there was practically no inbreeding depression.